2007
DOI: 10.1016/j.neulet.2007.03.020
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid in the second transmembrane domain of GABA ρ receptors regulates channel conductance

Abstract: GABAC receptors, expressed predominately in vertebrate retina, are thought to be formed mainly by GABA rho subunits, each of which exhibits distinct physiological and pharmacological properties. In this study, the receptors formed by perch GABA rho subunits were expressed in HEK cells, and their single channel conductances were determined using noise analysis techniques. The receptors formed by the perch rho1A subunit gate a channel with a conductance of 0.2 pS, whereas the receptors formed by GABA rho2 subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…3). In addition, using noise analysis techniques we estimated the single channel properties of the GABA C receptors present on rod bipolar cells; the derived values were comparable to those published previously (Feigenspan et al, 1993;Qian and Dowling, 1995;Palmer, 2006;Zhu et al, 2007). Although noise analysis tends to underestimate the value of single channel conductance, the same bias should apply results obtained from normal and diabetic cells.…”
Section: Discussionsupporting
confidence: 72%
“…3). In addition, using noise analysis techniques we estimated the single channel properties of the GABA C receptors present on rod bipolar cells; the derived values were comparable to those published previously (Feigenspan et al, 1993;Qian and Dowling, 1995;Palmer, 2006;Zhu et al, 2007). Although noise analysis tends to underestimate the value of single channel conductance, the same bias should apply results obtained from normal and diabetic cells.…”
Section: Discussionsupporting
confidence: 72%
“…The activation rate is roughly half that of wild type, and the deactivation rate is significantly decreased to one-fourth of the value for wild-type receptors. The 1 GABA C receptor used in this study has a single-channel conductance of Ͻ2 pS (26,27). The resulting small currents vitiate systematic kinetic studies using single-channel analysis.…”
Section: Resultsmentioning
confidence: 93%
“…Initially, we found that exchanging the N‐terminal extracellular domains of perch ρ1 and ρ2 subunits failed to alter the CTZ sensitivity profile (data not shown). However, it is important to recall that GABA ρ1 and ρ2 subunits exhibit a consistent difference at the 2′ position in the second transmembrane domain (Zhu et al 2007). The amino acid sequences of this region of the four perch ρ subunits (Fig.…”
Section: Resultsmentioning
confidence: 99%